Uses of the IMC tools for boosting the selling process: A study on Concord Entertainment Company Limited. - Bintay Nowsher, Sk. Fatima (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2022.